ASSESSING THE IMPACT OF THE WEIGHT OF THE TRAIN ON THE DYNAMIC LOADING OF THE ELECTROMECHANICAL ASYNCHRONOUS TRACTION DRIVE DURING THE SHORT CIRCUITS IN THE POWER SUPPLY OF STATOR WINDINGS - Bondariev, O. M. (Science and Transport Progress, 2003)
The article provides the results of theoretical calculations of short circuit emergency operation modes in supply circuits of the stator windings of asynchronous tractive motors at start-up of the locomotive, hauling a freight train.